Impact du pH du sol sur la flore adventice associée à la culture de haricot commun (Phaseolus vulgaris L.) cultivée dans l’hinterland de Lubumbashi, RD Congo = Impact of soil pH on the weed flora associated with common bean crop (Phaseolus vulgaris L.) grown in the hinterland of Lubumbashi, DR Congo - Assani Bin Lukangila, Mick; Kalombo Katwebe, Karine; Kirika Ansey, Bibich; Nsenga, Nkulu; Mwangalalo, Alal; Ekondo Okese, Augustin; Ilunga, Tshibingu Meschac; Ilunga Maloba, Maki; Mayuke Katshongo, Jean Paul; Kanyenga Lubobo, Antoine (2015)
Abstract: Weeds in our cultures are a constraint for farmers, which as far as possible combine a lot of effort to eradicate them. In addition to this aspect of nuisance, weeds could also be used for the prediction of soil fertility. Thus a floristic inventory study was conducted successively in 12 fields in the hinterland of Lubumbashi left on road 2axes: Kasumbalesa and Kipushi. Soil samples were collected in the forties randomly placed in the fields and then analyzed in the laboratory in order to identify the pH. The varied multi analyzes (PCA) have established a significant and positive correlation between the variables studied which would explain the invasion of the common bean culture despite the interventions of weeding. 24 species grouped into 7 families and 5 biological types including: therophytes 66.66%; Geophytes 12.5%; 8.33% hemicryptophytes, chamaephytes and finally Nanophanérophytes 4.16% proved tolerant of the pH tested (4.9 to 6.77) with (5.83) as an average value which allows farmers to have information not only in relation to different biological types defined but also on the distribution of weeds in relation to soil pH to ensure a good crop management by a successful weed management.